Multi-Agent Based Energy Management in Microgrids Using MACSimJX - Lakhina, U. (Institute of Electrical and Electronics Engineers Inc., 2019)
Excessive growth in electricity consumption has been experienced over the past few years due to an increase in population around the world.This tends to increase the use of renewable energy and randomness of the load. So.it is important to improve the traditional methodologies and techniques applied on microgrid to make it more intelligent. In this paper, multi agent system is employed over autonomous microgrid framework to endorse its intelligence. The Multi-Agent system is simulated in Java Agent Development Environment (JADE) environment and matlab toolbox Simulink is used for the implementation of the microgrid model. Further, MACSimJX is used to communicate between the micro grid and agent system. This paper shows the communication between the agents and the microgrid model and how they process the data through MACSimJX to make intelligent decisions. Â© 2019 IEEE.